Conservation status and management challenges of sub-Mediterranean grasslands in Bulgaria - Kazakova Y. (Ecosystem services and socio-economic benefits of Mediterranean grasslands, 2016)
Semi-natural grasslands are a key component of the EU Natura 2000 network and its second most threatened habitat group after wetlands. The tools available to ensure their sustainable management are placed within the EU Common Agricultural Policy. A new mechanism designating and supporting environmentally sensitive grasslands was introduced in the 2014-2020 period. The paper reviews the conservation status of the traditionally used for grazing Eastern sub-Mediterranean dry grasslands (code 62A0) in Bulgaria. In the 38 Natura 2000 sites where they are found, the combinations of the conservation status per parameter vary but the national conservation status is unfavourable-inadequate. Three sites are selected for an assessment of the CAP support eligibility of their permanent grasslands. The management challenges for ensuring favourable conservation status of semi-natural grasslands in the selected sites are: (i) overall declining levels of grazing; (ii) unresolved issues with permanent pastures definition and eligibility; (iii) lack of information on the habitat types in the agriculture datasets (iv) high share of municipal grasslands, which also have lower eligibility; (v) each municipality has its own pastures management rules and procedures, which complicates the situation in larger Natura 2000 sites.
15. Meeting of the Mediterranean Sub-Network of the FAO-CIHEAM International Network for the Research and Development of Pastures and Fodder Crops, 2016/04/12-14, Orestiada (Greece)